SKILL VS DEGREE: RELEVANSI GELAR AKADEMIK DALAM DINAMIKA PASAR KERJA KONTEMPORER - Supriatna, Dasep (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The implications of this debate are significant for individuals in planning career paths, educational institutions in designing curricula, and employers in their talent management strategies. While academic degrees are still often seen as a foundation of knowledge and evidence of learning ability and commitment, employers are increasingly prioritizing candidates who can demonstrate applied competencies relevant to immediate operational needs. This research investigates the comparative relevance between practical skills and academic degrees in the contemporary Indonesian job market, using Human Capital Theory as a foundation. Through a mixed-methods comparative design (surveys, interviews, content analysis) of employers, job seekers and employees, the study found significant preference shifts. Results show employers consistently prioritize practical relevant skills in recruitment and compensation determination, although a degree is still considered important as an initial foundation. Skills proved to be a stronger predictor of recruitment success.